2010
DOI: 10.1118/1.3515839
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific radiation dose and cancer risk estimation in CT: Part I. Development and validation of a Monte Carlo program

Abstract: Purpose: Radiation-dose awareness and optimization in CT can greatly benefit from a dosereporting system that provides dose and risk estimates specific to each patient and each CT examination. As the first step toward patient-specific dose and risk estimation, this article aimed to develop a method for accurately assessing radiation dose from CT examinations. Methods: A Monte Carlo program was developed to model a CT system ͑LightSpeed VCT, GE Healthcare͒. The geometry of the system, the energy spectra of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 42 publications
2
95
1
Order By: Relevance
“…In our previous study (17,22), we reported the development and validation of a Monte Carlo program for simulating dose with a 64-section CT system (LightSpeed VCT; GE Healthcare, Waukesha, Wis). The program was based on a benchmarked Monte Carlo subroutine package for photon, electron, and positron transport (PE-NELOPE, version 2006; Universitat de Barcelona, Barcelona, Spain) (23,24).…”
Section: Ct Examination Simulationsmentioning
confidence: 99%
“…In our previous study (17,22), we reported the development and validation of a Monte Carlo program for simulating dose with a 64-section CT system (LightSpeed VCT; GE Healthcare, Waukesha, Wis). The program was based on a benchmarked Monte Carlo subroutine package for photon, electron, and positron transport (PE-NELOPE, version 2006; Universitat de Barcelona, Barcelona, Spain) (23,24).…”
Section: Ct Examination Simulationsmentioning
confidence: 99%
“…Christ et al 28 constructed the virtual family models including the 6-yr-old male and 7-yr-old female. Nagaoka et al 29 developed 3-, 5-, and 7-yr-old Japanese children models, whereas Li et al 30 developed two pediatric phantoms based on a 5-week-old girl and a 12-yr-old boy. Nipper et al 31 and Lee et al 32,33 of the University of Florida elaborated a series of pediatric voxel models of various ages.…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic dose variation near the periphery of a scanned volume, which was caused by different tube starting angles alone, has also been reported in the literature. 22,23,43 This characteristic of the helical CT scans created a random factor into our point dose measurements.…”
Section: Resultsmentioning
confidence: 99%
“…With the advances in both computational phantoms and modeling of CT systems, several research groups have worked on more patientspecific CT dose estimation methods. [20][21][22][23][24][25][26] One such software is the VirtualDose (www.virtual-dose.com) that employs a library of adult and pediatric patient phantoms for organ dose reporting.…”
Section: Introductionmentioning
confidence: 99%